2017
DOI: 10.4103/1119-3077.180069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of manual and mechanical instrumentation techniques for removal of overextended root canal filling material

Abstract: This study demonstrated that all tested systems had similar efficacy in removing overextended root canal filling material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The primary objective of retreatment is to remove root canal filling materials, disinfect the root canal system, and obturate the root canals [ 20 ]. Removal of root canal filling material from the apical third is the most difficult part of retreatment because of the anatomic variability of the apical third [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of retreatment is to remove root canal filling materials, disinfect the root canal system, and obturate the root canals [ 20 ]. Removal of root canal filling material from the apical third is the most difficult part of retreatment because of the anatomic variability of the apical third [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This investigation was conducted across eighty previously extracted mandibular premolar teeth, divided into four study groups according to the applied manual and mechanical methods. (Kesim et al, 2017). The results of this investigation demonstrated that none of the differing manual and mechanical methodologies had any additional efficacybased advantage over the remainder groups, with Hedstrom files exhibiting a non-statistically significant success rate compared to the remainder study groups (Kesim et al, 2017).…”
Section: Mechanical Gp Removal Methodologies A) Hedstrom Filesmentioning
confidence: 78%
“…(Kesim et al, 2017). The results of this investigation demonstrated that none of the differing manual and mechanical methodologies had any additional efficacybased advantage over the remainder groups, with Hedstrom files exhibiting a non-statistically significant success rate compared to the remainder study groups (Kesim et al, 2017). However, Hedstrom files, a highly manual form of GP removal technique, carry disadvantages, mainly concerning dentin losses during the procedure.…”
Section: Mechanical Gp Removal Methodologies A) Hedstrom Filesmentioning
confidence: 81%
See 1 more Smart Citation
“…Eliminating previous obturating substances, left over necrosed tissues plus bacteria, re-instrumentation, disinfecting, and obturating the canals are the chief purposes of re-therapy. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%